해외 온라인 3D프린팅 플랫폼 분석을 통한 국내 온라인 3D프린팅 마켓플레이스 전망 - 송민정; Song Min Jeong; 하은아; Ha Euna Ewha; 김효정; Kim Hyo Jung; 조재경; Cho Jae Ewha (기초조형학연구, 2016)
최근 3D프린팅과 그에 연계된 제조산업의 발전방향에 대한 관심이 고조되고 있으며, 예술·디자인 분야에서도 신 디지털 제조기술을 활용한 새로운 패러다임 구축을 목표로 창의·산업분야에 연구를 집중하고 있다. 3D프린팅 기술은 디지털 콘텐츠를 사용하여 출력하는 매커니즘을 갖고 있기 때문에 디자이너들에게는 디지털 창작물을 공개 및 판매할 수 있는 새로운 마켓플레이스로 성장할 수 있는 가능성을 보이고 있다. 하지만 현재까지 하드웨어 기술에의 편향적인 관심으로 인해 디지털 직접제조를 통한 새로운 콘텐츠 양산에 관한 학술연구가 상대적으로 미비하기 때문에 디지털 콘텐츠 제작과 그 유통에 관한 연구가 중요한 시점이다. 이에 본 연구에서는 3D프린팅 온라인 플랫폼/마켓플레이스에 대한 현황조사를 기반으로 기초연구를 통하여 국내의 3D프린팅 콘텐츠 분야 개발과 유통의 발전 방향을 제시하는데 목적이 있다. 연구방법으로는 문헌과 선행연구, 메타데이터 분석을 통하여 연구대상 온라인 플랫폼을 도출하였으며, 이를 통해 웹기반 3D프린팅 플랫폼의 장단점을 분석하였다. 연구결과를 정리하면 다음과 같다. 현재까지 3D프린팅 기술이 대중화된 단계가 아니기 때문에 디자인과 출력을 대행하고 중개해주는 일반소비자 중심의 플랫폼이 필요한 시기로 분석된다. 따라서 무료 공유파일을 부분적으로 제공하되 동시에 보다 품질이 뛰어난 유료 파일을 판매함으로써 소비자의 요구를 만족시키고, 디지털직접제조 문화의 대중화에 노력을 기울어야 한다. 또한 웹기반의 인터페이스를 발전시켜서 소비자들이 직접 디자인 모델링에 참여할 수 있도록 하는 무료 소프트웨어를 제공하는 것도 필히 개선해야 할 것이다. 상대적으로 3D프린팅 기술이 활성화되지 않은 국내에서는 3D프린팅 하드웨어 기술에 대한 연구 뿐 아니라, 그에 따른 콘텐츠 개발에 관한 지속적인 연구가 필요할 것으로 전망한다. As desktop 3D printers have become available in recent years, the potential for personal fabrication has increased. 3D printing technologies provide opportunities for designers and makers to enter a new marketplace run with digital contents. Accordingly, global online 3D printing platforms have emerged to share 3D files and knowledge among professional and amateur makers. However, such online infrastructures are hardly visible in the domestic scene despite the attention given to the technology by the public. Thus, this research investigates into the role of online platforms in the dissemination of 3D printing technologies, and it attempts to provide a perspective on the development of Korea-based online platforms dedicated to 3D printing. The research scope has been defined through the meta-analysis of 3D printing demographics and literature review. Drawing on the analyses of internationally-established online 3D file repositories and marketplaces for 3D printing, the research findings are as follows. As well as disseminating free files to general users for trials, online platforms would need to hire professional designers to provide high-quality files with a fee. Also, the development of web-based online 3D modeling software applications for user-created contents would be an essential feature for the democratization of the technology. More attention would need to be given to the development of digital contents rather than solely focusing on the technology itself.